2001
DOI: 10.1089/153036601753552594
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vectorial Capacity of Anopheles dirus (Diptera: Culicidae) in a Forest-Fringed Village of Assam (India)

Abstract: To estimate the vectorial capacity of Anopheles dirus, the main vector of forest malaria in the northeastern region of India, in order to gain an understanding of entomological factors related to malaria transmission in forest-fringe areas of Assam, India, an isolated village in the tropical rain forest-fringed area in the district of Dibrugarh, Assam, under the influence of An. dirus alone was studied. Data on various entomological variables required for computation of the vectorial capacity were generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 3 publications
1
26
0
Order By: Relevance
“…In an isolated village in a tropical rain forest-fringe area in Assam, India, the vectorial capacity of An. baimaii for P. vivax was higher than for P. falciparum during the monsoon season, decreasing in post monsoon and reaching zero in the cold and dry season (Prakash et al 2001). In Naga Hills, India, the prevalence of malaria is related to the vector density thus it was higher in localities closer to the forest where An.…”
Section: Anopheles (Cellia) Baimaiimentioning
confidence: 88%
See 1 more Smart Citation
“…In an isolated village in a tropical rain forest-fringe area in Assam, India, the vectorial capacity of An. baimaii for P. vivax was higher than for P. falciparum during the monsoon season, decreasing in post monsoon and reaching zero in the cold and dry season (Prakash et al 2001). In Naga Hills, India, the prevalence of malaria is related to the vector density thus it was higher in localities closer to the forest where An.…”
Section: Anopheles (Cellia) Baimaiimentioning
confidence: 88%
“…leucosphyrus , An. baimaii (Rahman et al 1977;Rosenberg & Maheswary 1982b;Dutta et al 1991;Prakash et al 2001), An. dirus (Eyles et al 1964;Scanlon & Sandhinand 1965;Sloof & Verdrager 1972;Ismail et al 1974Ismail et al ,1975Wilkinson et al 1978;Deng et al 1982;Trung et al 2004), and An.…”
mentioning
confidence: 99%
“…P. vivax and P. falciparum are commonly found in An. baimaii (Sallum et al, 2005;Obsomer et al, 2007), but original sources do not differentiate the members of the Dirus Complex (Prakash et al, 2001). An.…”
Section: Asiamentioning
confidence: 99%
“…The vectorial capacity of An. dirus for P. vivax has been estimated (Prakash et al, 2001). Experimental infection from humans (Wirtz et al, 1985), monkeys (Collins et al, 2009) and membrane feeding has been shown (Coleman et al, 2004;Junkum et al, 2005).…”
Section: An Dirus Complex Yesmentioning
confidence: 99%
“…is responsible for hyper-endemic malaria (Rosenberg and Maheswari 1982) and its importance as an efficient malaria vector in the northeastern states of India was well documented (Sen et al 1973;Dutta et al 1989). Prakash et al (1997) reported that deep forest areas in northeastern India offer favourable breeding grounds for this species and that the abundance is determined by the pattern of rainfall. Hence, the villages near the forest, which are under the influence of An.…”
Section: Discussionmentioning
confidence: 99%